Activity‐dependent synaptic integration and modulation of bilateral excitatory inputs in an auditory coincidence detection circuit. (16th April 2018) - Lu, Yong; Liu, Yuwei; Curry, Rebecca J.
Abstract : Key points: Binaural excitatory inputs to coincidence detection neurons in nucleus laminaris (NL) play essential roles in interaural time difference coding for sound localization. Here, we show that the two excitatory inputs are physiologically nearly completely segregated. Synaptic integration shows linear summation of EPSPs, ensuring high efficiency of coincidence detection of the bilateral excitatory inputs. We further show that the two excitatory inputs to single NL neurons are symmetrical in synaptic strength, kinetics and short‐term plasticity. Modulation of the EPSCs by metabotropic glutamate receptors (mGluRs) is identical between the two excitatory inputs, maintaining balanced bilateral excitation under neuromodulatory conditions. Unilateral hearing deprivation reduces synaptic excitation and paradoxically strengthens mGluR modulation of EPSCs, suggesting activity‐dependent anti‐homeostatic regulation, a novel synaptic plasticity in response to sensory manipulations. Abstract: Neurons in the avian nucleus laminaris (NL) receive bilateral excitatory inputs from the cochlear nucleus magnocellularis, via morphologically symmetrical dorsal (ipsilateral) and ventral (contralateral) dendrites. Using in vitro whole‐cell patch recordings in chicken brainstem slices, we investigated synaptic integration and modulation of the bilateral inputs to NL under normal and hearing deprivation conditions. We found that the two excitatory inputs onto single NL neurons were nearly completely segregated, and integration of the two inputs was linear for EPSPs. The two inputs had similar synaptic strength, kinetics and short‐term plasticity. EPSCs in low but not middle and high frequency neurons were suppressed by activation of group I and II metabotropic glutamate receptors (mGluR I and II), with similar modulatory strength between the ipsilateral and contralateral inputs. Unilateral hearing deprivation by cochlea removal reduced the excitatory transmission on the deprived dendritic domain of NL. Interestingly, EPSCs evoked at the deprived domain were modulated more strongly by mGluR II than at the counterpart domain that received intact input in low frequency neurons, suggesting anti‐homeostatic regulation. This was supported by a stronger expression of mGluR II protein on the deprived neuropils of NL. Under mGluR II modulation, EPSCs on the deprived input show transient synaptic facilitation, forming a striking contrast with normal hearing conditions under which pure synaptic depression is observed. These results demonstrate physiological symmetry and thus balanced bilateral excitatory inputs to NL neurons. The activity‐dependent anti‐homeostatic plasticity of mGluR modulation constitutes a novel mechanism regulating synaptic transmission in response to sensory input manipulations. Key points: Binaural excitatory inputs to coincidence detection neurons in nucleus laminaris (NL) play essential roles in interaural time difference coding for sound localization. Here, we show that the two excitatory inputs are physiologically nearly completely segregated. Synaptic integration shows linear summation of EPSPs, ensuring high efficiency of coincidence detection of the bilateral excitatory inputs. We further show that the two excitatory inputs to single NL neurons are symmetrical in synaptic strength, kinetics and short‐term plasticity. Modulation of the EPSCs by metabotropic glutamate receptors (mGluRs) is identical between the two excitatory inputs, maintaining balanced bilateral excitation under neuromodulatory conditions. Unilateral hearing deprivation reduces synaptic excitation and paradoxically strengthens mGluR modulation of EPSCs, suggesting activity‐dependent anti‐homeostatic regulation, a novel synaptic plasticity in response to sensory manipulations.